ANALYSIS OF THE SELECTION OF NAVAL BASES IN THE HANDLING OF PIRACY AND PIRACY CRIMES BY MEANS OF FUZZY AHP, TOPSIS AND GIS - Okol Sri Suharyo; Eko Nur Yasin; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Piracy and piracy incidents that often occur in Indonesian waters greatly affect the credibility and dignity of the Indonesian nation in the eyes of the international world. Based on existing data, piracy and piracy in Indonesian waters became the most in the world, especially in the waters of the Strait of Malacca. This condition certainly has a negative impact on the Indonesian government. Even the International Maritime Bureau (IMB) gave the title